(untitled) (Journal of Educational Sciences, 2016)
Today, researchers distinguish between two types of innovation phenomena in education: pedagogical innovation (innovations in education) and innovative training. The purposeful formation of readiness of future teachers to innovative activity requires the creation of such conditions: – high level formed readiness for innovative activity of teachers engaged in the process of preparation of future teachers; – inclusion of future teachers in real practice innovation education by alternating individual consultations, creative tasks), group (lectures, seminars) and collective (role play, discussions, trainings) forms of training, aimed at the formation of readiness for innovative activity;– mastering of future teachers in the techniques of reflective analysis of their own activities; – application in the educational process of information technology to create a shortcut, projective educational situations. Given the characteristics of innovation in education and the demands of the modern teacher, there are two main areas of preparation of future teachers to innovative activity: – associated with planning and organization of innovative educational process; – associated with the development of personal and professional qualities of future teachers needed for innovation. Recommendations on the implementation of these directions.